Live Streaming Experience and Offline Purchase Intent: The Role of Flow Experience and Environmental Design in the Indonesia Skincare Industry within the SOR Framework - Diya Aldin Fadeyushka; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
This study examines the impact of In-store Live Streaming (SLS) on Offline Purchase Intention (OPI) within the Indonesian skincare industry, utilizing the Stimulus-Organism-Response (SOR) framework. The research specifically investigates the role of Scene-Product Congruence (SPC) and Wishful Identification (WI), as they influence Flow Experience (FE) and Attitude Toward Product (ATP), and ultimately affect OPI, with Consumer Informedness (CI) as a moderator. Analysing data from a self-reported online questionnaire using Structural Equation Modelling-Partial Least Squares (SEM-PLS), the study reveals that SPC significantly enhances FE, which subsequently fosters a positive ATP and leads to higher OPI. However, the effects of Visual Appeal and WI on FE were found to be weak. This indicates that skincare consumers prioritize visual relevance and product credibility over pure aesthetics and wishful identification in the in-store live streaming (SLS) context. Furthermore, CI's negative impact on OPI is not significant, suggesting that well-informed consumers can maintain a positive ATP despite a potential unwillingness to engage in offline sales interaction. This research offers practical insights, emphasizing the need for digital commerce strategies to prioritize the relevance and informational coherence of the live streaming scene to achieve a meaningful consumer experience and sustainable brand loyalty.